Sustainability of subsistence livelihoods of agro-pastoralists in changing socioeconomic environment of Cholistan desert-Pakistan - Sher Muhammad Malik; Fazlur-Rahman; Amjad Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
Subsistence livelihoods of agro-pastoralists are heavily dependent on vulnerable natural resources. These natural resources are exposed to a number of risks in the form of shocks, trends and seasonality. These risks are linked with environmental hazards. The Cholistan desert is divided into Greater and Lesser Cholistan. Based on 2016 population estimation, thirty settlements were selected with proportion of 30% and 70% from greater and lesser Cholistan, respectively. The socioeconomic changes and their impact on livelihood strategies were studied. Human practices (transhumance and nomadism), land uses, population & settlement growth and living standards are the key indicators of the socioeconomic changes. Modern technologies, policy and hazards brought transformations in the livelihoods patterns in the Cholistan desert. The sustainability of subsistence livelihoods of agro-pastoralists in Cholistan desert was analyzed through strength, weaknesses, opportunities and threats (SWOT) technique. In the lesser Cholistan, transformation in sustainability of livelihoods prevail in positive realm. However, in greater Cholistan which is the marginalized areas of Cholistan desert, this transformation both in socio-economic and physical set up are pushing the poor agro-pastoral communities towards vulnerability. The resilience of these subsistence livelihoods of agro-pastoralists can be enhanced through adaptation of innovative techniques and synchronization of land resettlement policy.
Keywords: 330; productive and sustainable land management; sustainability; livelihoods; agro-pastoralists; Cholistan desert; SWOT analysis